Adjustment Disorder in the Spouses of Individuals with Alcohol Use Disorders (International Journal of Food and Nutritional Sciences, 2022)
Background: Alcoholism is regarded to be the most significant health and social concern. It affects not just the person but also the entire family. The wives of patients with alcohol use disorders are the most negatively affected, resulting in significant psychological issues. The purpose of this study is to evaluate adjustment disorder in wives of patients with alcohol use disorders. Aim’s & objectives: Hospital-based cross-sectional research. Psychiatry department/De-addiction centre of a tertiary care medical college and hospital in Rajasthan. Alcohol Dependence-diagnosed individuals attending the department of psychiatry are studied with their spouses. Material and Procedure: Sixty participants were investigated based on inclusion and exclusion criteria. According to the standardised pro forma, demographic data and psychiatric disease history were recorded. The GHQ-12 was utilised to screen for mental comorbidity. Participants scoring >2 on the GHQ-12 were further evaluated by the psychiatrist for the existence of adjustment disorder and were classified according to ICD-10 diagnostic criteria.Results: According to ICD-10, fifteen (25%) participants were diagnosed with an adjustment disorder. The most prevalent subtype of adjustment disorder was adjustment disorder with mixed anxiety and depression reaction (60%), followed by adjustment disorder with extended depressive reaction (20%) and significant disturbance of other emotions (20%).Conclusion: The current study suggests that the wives of patients with Alcohol Use Disorders suffer substantial psychological co morbidities. The most prevalent diagnosis among adjustment disorders was adjustment disorder with mixed anxiety and depressed reaction.